Penerapan Doktrin Identifikasi dalam Menentukan Pertanggungjawaban Pidana Korporasi Atas Tindak Pidana Korupsi - Ilhan Nurdipa; Anita Zulfiani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the extent to which the identification doctrine is applied in establishing corporate criminal liability for acts of corruption. The increasing number of corruption cases involving corporate entities poses a challenge for the criminal justice system in attributing legal fault to legal persons that lack independent intent or will. The objective of this research is to analyze how the identification doctrine is utilized to bridge this issue and to assess its effectiveness and fairness in judicial practice. This study employs a normative legal approach using qualitative methods through the analysis of statutory regulations, legal doctrines, and court decisions. The findings indicate that although the identification doctrine provides a logical foundation for prosecuting corporations through the actions of their directors or executives, its application still faces challenges in distinguishing between individual actions taken personally and those undertaken on behalf of the corporation. This ambiguity may result in legal uncertainty and injustice in the enforcement of criminal sanctions. Therefore, clear and firm criteria are necessary in determining corporate criminal liability to support a more just and accountable legal system.